A method for preparing fluorine / carbon co-doped titanium dioxide noble metal cluster photocatalyst material
Through the preparation of fluorine/carbon co-doped titanium dioxide noble metal cluster photocatalyst materials, the problems of low efficiency and environmental pollution of titanium dioxide-supported precious metal catalysts in the prior art are solved, and high-efficiency photocatalytics and material stability are improved under visible light. In the industrial production of photocatalyst materials.
Patent Information
- Application Number
- CN202310441485.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-23
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-04-23
AI Technical Summary
In the preparation process of existing titanium dioxide-supported precious metal catalysts, there are problems such as low efficiency, unfriendly preparation environment and unstable product performance, especially inadequate impregnation, which leads to uneven loading, affecting photocatalytic efficiency.
The preparation method of fluorine/carbon co-doped titanium dioxide noble metal cluster photocatalyst material is used to form a hydrothermal reaction between titanium salt, fluorine source, noble metal salt and solvent and surfactant after multiple washing, centrifugation, drying and calcination. The highly catalytically active fluorine/carbon co-doped titanium dioxide noble metal cluster photocatalyst material has a sponge-like wrinkle structure on the surface, which improves the specific surface area and photocatalytic capacity of the material.
It realizes efficient photocatalysis under visible light, degradation of organic pollutants, simplifies the preparation process, reduces the cost of reagents, facilitates large-scale production, and improves the stability and catalytic efficiency of materials.
Smart Images

Figure CN116459830B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material preparation and relates to a method for preparing a fluorine / carbon co-doped titanium dioxide noble metal cluster photocatalyst material. Background Art
[0002] Titanium dioxide is a simple and easily available photocatalyst material. There are many practical products and preparation schemes in the photocatalytic coatings and dyes industries. Titanium dioxide has excellent properties such as strong catalytic ability and easy batch preparation. These excellent properties make titanium dioxide products widely used in building exterior wall decontamination, decoration coatings, indoor air cleaning and other fields. The optimization of its photocatalytic performance and product performance is one of the difficult problems in the coatings industry. The absorption sideband of titanium dioxide is located in the ultraviolet light region, and there is almost no light absorption in the near-infrared light region. The content of ultraviolet light in natural light is less than 5%, which seriously affects the photocatalytic effect of titanium dioxide. This means that in order to improve the photocatalytic efficiency of titanium dioxide, it is necessary to try to expand the light absorption range of titanium dioxide to the visible light region where it exists in large quantities, further optimize the performance of photocatalyst materials, and improve the technical solutions of photocatalyst materials.
[0003] Doping is one of the common methods for preparing composite materials. Fluorine doping can effectively improve the response efficiency of photocatalyst materials, produce a sideband red shift effect, and play a role in regulating the crystal form during the crystallization of titanium dioxide. At the same time, high catalytic activity titanium dioxide nanopowder can be obtained by changing the preparation conditions. Precious metal composites can redistribute the carriers on the surface of titanium dioxide materials, so that precious metal atoms can serve as reactive active sites, inhibit the recombination of photogenerated electrons and holes, and effectively improve the catalytic efficiency of photocatalyst materials.
[0004] Chinese patent CN 106076375 A. discloses a fluorine-doped titanium dioxide-loaded precious metal catalyst and its preparation method and application. The patent uses titanium dioxide powder as a carrier, directly uses an aqueous solution of HF or NaF for impregnation and roasting, and further uses a precursor solution of a precious metal for impregnation and roasting. The invention provides a preparation scheme for a fluorine-doped titanium dioxide-loaded precious metal catalyst, which is simple and feasible, but the preparation process is not fully impregnated, which easily causes uneven loading of the prepared catalyst, unstable product performance, and easy to cause environmental pollution, and is not easy to implement industrial production.
[0005] In summary, titanium dioxide-loaded precious metal catalysts still have problems such as low efficiency and unfriendly preparation environment. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention provides a method for preparing a fluorine / carbon co-doped titanium dioxide noble metal cluster photocatalyst material.
[0007] To achieve the above object, the technical solution of the present invention is as follows:
[0008] In the first aspect, the present invention provides a fluorine / carbon co-doped titanium dioxide precious metal cluster photocatalyst material. The fluorine / carbon co-doped titanium dioxide precious metal cluster photocatalyst material is a white or off-white powder, which is made of titanium salt, fluorine source, and precious metal salt as raw materials, and is mixed with solvents and surfactants. The mixture is transferred to a polytetrafluoroethylene reactor for hydrothermal reaction, and is obtained by multiple washing, centrifugation, drying, and calcination.
[0009] In a second aspect, the present invention provides a method for preparing a fluorine / carbon co-doped titanium dioxide precious metal cluster photocatalyst material, the method comprising: taking titanium salt, fluorine source, and precious metal salt as raw materials, adding a solvent and a surfactant and mixing them evenly, transferring them to a polytetrafluoroethylene reactor for hydrothermal reaction, and obtaining a fluorine / carbon co-doped titanium dioxide precious metal cluster photocatalyst material after multiple washing, centrifugation, drying, and calcination; the mass ratio of the titanium salt, fluorine source, precious metal salt, solvent, and surfactant is: (0.115-0.175):(0.003-0.005):(0.003-0.005):(0.85-0.95):(0.002-0.004), and the temperature of the hydrothermal reaction is 110°C-190°C.
[0010] Preferably, the titanium salt is one of titanium tetrachloride and tetrabutyl titanate; the fluorine source is one of sodium fluoride, lithium fluoride and hydrofluoric acid; the noble metal salt is one of silver salt and platinum salt; the solvent is a mixed solution of nitric acid or hydrochloric acid with deionized water and ethanol; and the surfactant is a thiol ligand.
[0011] Preferably, the volume ratio of the nitric acid or hydrochloric acid: deionized water: ethanol is: (0.02-0.2): (0.1-0.4): (0.4-0.8).
[0012] Preferably, the surfactant is one of n-octyl mercaptan, 2-naphthyl mercaptan, n-pentyl mercaptan, and mercapto-triethylene glycol-carboxylic acid.
[0013] Preferably, in the fluorine / carbon co-doped titanium dioxide precious metal cluster photocatalyst material, the fluorine element is doped into the titanium dioxide lattice in the form of atoms or ions or is compounded with titanium dioxide in the form of compounds, and the precious metal salt is deposited on the surface of the composite material in the form of nanoclusters. The surface of the fluorine / carbon co-doped titanium dioxide precious metal cluster photocatalyst material presents a special sponge-like wrinkled structure.
[0014] Preferably, after the titanium salt, fluorine source and precious metal salt are uniformly mixed, a solvent and a surfactant are added and mixed evenly, and then transferred to a polytetrafluoroethylene reactor, the titanium salt is hydrolyzed into titanium dioxide by a hydrothermal reaction, and fluorine / carbon co-doping and precious metal salt compounding are simultaneously achieved to obtain fluorine / carbon co-doped titanium dioxide precious metal cluster photocatalyst material, which is centrifuged in a centrifuge, and then washed with deionized water and anhydrous ethanol for multiple times, dried, and calcined to obtain a white or off-white powder.
[0015] Preferably, the method comprises the following steps:
[0016] Step (1): add 20 mL-30 mL of solvent into beaker 1, add 6 g-8 g of titanium salt thereto, put a magnetic rotor into beaker 1, and place beaker 1 on a magnetic stirrer to stir and disperse at a uniform speed for later use;
[0017] Step (2): Take another beaker 2, add 0.05g-0.25g of fluorine source and 10mL-20mL of solvent and shake well, transfer the solution in beaker 2 to beaker 1, and disperse at room temperature using magnetic stirring for 5min-10min to obtain a mixed solution;
[0018] Step (3): transferring the mixed solution obtained in step (2) to a hydrothermal reactor with a polytetrafluoroethylene liner to perform a hydrothermal reaction at a temperature of 130° C. to 190° C. for a time of 2 h to 6 h. After the reaction is completed, a liquid with a light pink precipitate is obtained. The upper clear liquid is removed at rest, and the light pink precipitate is washed with water and alcohol for multiple times, then centrifuged and dried in an oven at 40° C. to 60° C.;
[0019] Step (4): the light pink powder obtained in step (3) is transferred to beaker 3, 0.05 g to 0.25 g of noble metal salt, 30 mL of solvent, and 0.035 g to 0.4 g of surfactant are added, and after being fully mixed, the mixture is transferred to a hydrothermal reactor lined with polytetrafluoroethylene for hydrothermal reaction. The hydrothermal reaction temperature is 110° C. to 170° C., and the hydrothermal reaction time is 2 h to 8 h. After the reaction is completed, a liquid with an off-white precipitate is obtained;
[0020] Step (5): centrifuge the liquid with off-white precipitate obtained in step (4) to obtain an off-white powder, wash the off-white powder with water and alcohol for multiple times, and place it in an oven at 40° C.-60° C. to dry it for 12-24 hours;
[0021] Step (6): calcine the preliminary product obtained in step (5) at 300-600° C. in a nitrogen atmosphere for 1-3 h, and continue to calcine for 1-3 h while introducing air to obtain a product, namely, a fluorine / carbon co-doped titanium dioxide noble metal cluster photocatalyst material.
[0022] The present invention has the following beneficial effects:
[0023] (1) The present invention adopts a two-step solvothermal method to prepare fluorine / carbon co-doped titanium dioxide noble metal cluster photocatalyst materials, and the experimental scheme is simple and the operation steps are easy to perform.
[0024] (2) The titanium dioxide photocatalyst material prepared by the present invention has a high photocatalytic ability under visible light and with a small amount, and can be used as a photocatalyst material to degrade organic pollutants under visible light.
[0025] (3) The reagents used in the present invention are low in cost and convenient for large-scale production.
[0026] (4) The surface of the titanium dioxide photocatalyst material prepared by the present invention has a special sponge-like wrinkled structure, which increases the specific surface area of the material and improves the catalytic ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the SEM spectrum of the fluorine / carbon co-doped titanium dioxide noble metal cluster photocatalyst prepared in Example 1 of the present invention;
[0028] Figure 2 This is the XRD spectrum of the fluorine / carbon co-doped titanium dioxide noble metal cluster photocatalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below in conjunction with specific implementation methods.
[0030] Embodiment 1:
[0031] 1) quantitatively measure 20 mL of ethanol and transfer it to a 100 mL beaker 1, weigh 6 g of tetrabutyl titanate and transfer it to the beaker 1, measure 5 mL of nitric acid and add it to the beaker 1, put a magnetic rotor into the beaker 1, and place it on a magnetic stirrer for stirring for later use;
[0032] 2) Take another 100mL beaker 2, weigh 0.15g lithium fluoride and add it to beaker 2, add 10mL deionized water and stir to dissolve for 5min, transfer to beaker 1, stir for 5min under uniform stirring to obtain a mixed solution;
[0033] 3) The mixed solution obtained above was transferred to a polytetrafluoroethylene liner, placed in a hydrothermal reactor, and reacted at 150° C. in a constant temperature oven for 4 hours to obtain a light pink precipitate; the precipitate was transferred to a centrifuge tube, centrifuged 3 times with deionized water, and then centrifuged 2 times with anhydrous ethanol for later use;
[0034] 4) Weigh 0.15g of silver nitrate and add it to beaker 3, add 10mL of deionized water and stir to dissolve, add 0.08g of n-octyl mercaptan and the precipitate obtained by centrifugation in step 3), and ultrasonically disperse for 10 minutes. Transfer the dispersed solution to a polytetrafluoroethylene liner, place it in a hydrothermal reactor, and react at a constant temperature of 130°C in a constant temperature oven for 6 hours to obtain a white or off-white precipitate;
[0035] 5) The precipitate was transferred to a centrifuge tube, centrifuged three times with deionized water, and then centrifuged twice with anhydrous ethanol, and dried in a forced air oven at 60°C to obtain an off-white powder sample, which was calcined at 500°C in a nitrogen atmosphere for 1 hour, and then calcined for 1 hour with air introduced to obtain a photocatalyst product.
[0036] 6) Organic dye removal test: 0.1g of the obtained powder sample was mixed with methylene blue solution (10mg / L) in groups, and stirred at a constant speed of 300r / min under 800W ultraviolet light and natural light respectively. After 30min, 1h, and 2h, samples were taken to detect the dye concentration. The test results are as follows:
[0037]
[0038] 0.1g of the obtained powder sample was mixed with rhodamine B solution (10mg / L) in groups, and stirred at a constant speed of 300r / min under 800W ultraviolet light and natural light respectively. After 30min, 1h, and 2h, samples were taken to detect the dye concentration. The test results are as follows:
[0039]
[0040]
[0041] After testing, the fluorine / carbon co-doped titanium dioxide noble metal cluster photocatalyst powder obtained in Example 1 has ultraviolet light absorption activity and visible light absorption activity. It has certain photocatalytic activity under visible light and can be used as a photocatalyst material to degrade organic dyes under visible light.
[0042] Figure 1 This is a SEM spectrum of the fluorine / carbon co-doped titanium dioxide noble metal cluster photocatalyst prepared in Example 1 of the present invention. From the figure, it can be clearly seen that the present invention has a unique sponge-like wrinkled surface morphology formed by the accumulation of titanium dioxide microspheres, and the Ag atomic particles are evenly embedded on the wrinkled surface.
[0043] Figure 2This is the XRD spectrum of the fluorine / carbon co-doped titanium dioxide precious metal cluster photocatalyst prepared in Example 1 of the present invention. It can be seen from the figure that the peaks at 25.3°, 37.8°, and 48° correspond to the (101) (004) (200) crystal planes of anatase titanium dioxide, respectively; the peaks at 27.5° and 36.1° belong to the (110) and (101) crystal planes of rutile titanium dioxide, respectively; the three peaks at 38.2°, 44.3°, and 64.5° belong to single substance Ag, and there are no other crystal peaks in the spectrum, indicating that anatase titanium dioxide, rutile titanium dioxide, and single substance Ag exist in the sample at the same time.
[0044] Embodiment 2:
[0045] 1) quantitatively measure 20 mL of ethanol and transfer it to a 100 mL beaker 1, weigh 6 g of titanium tetrachloride and transfer it to the beaker 1, measure 5 mL of hydrochloric acid and add it to the beaker 1, put a magnetic rotor into the beaker 1, and place it on a magnetic stirrer for stirring for later use;
[0046] 2) Take another 100mL beaker 2, weigh 0.15g of sodium fluoride and add it to beaker 2, add 10mL of deionized water and stir to dissolve for 5min, transfer to beaker 1, stir at a constant speed for 5min to obtain a mixed solution;
[0047] 3) The mixed solution obtained above was transferred to a polytetrafluoroethylene liner, placed in a hydrothermal reactor, and reacted at 130° C. in a constant temperature oven for 6 hours to obtain a light pink precipitate; the precipitate was transferred to a centrifuge tube, centrifuged 3 times with deionized water, and then centrifuged 2 times with anhydrous ethanol for later use;
[0048] 4) Weigh 0.15g of silver nitrate and add it to beaker 3, add 10mL of deionized water and stir to dissolve, add 0.1g of 2-naphthyl mercaptan and the precipitate obtained by centrifugation in step 3), and ultrasonically disperse for 10min. Transfer the dispersed solution to a polytetrafluoroethylene liner, place it in a hydrothermal reactor, and react at 150°C in a constant temperature oven for 4h to obtain a white or off-white precipitate;
[0049] 5) The precipitate was transferred to a centrifuge tube, centrifuged three times with deionized water, and then centrifuged twice with anhydrous ethanol, and dried in a forced air oven at 60°C to obtain an off-white powder sample, which was calcined at 400°C in a nitrogen atmosphere for 1 hour, and then calcined for 1 hour with air introduced to obtain a photocatalyst product.
[0050] 6) Organic dye removal test: 0.1g of the obtained powder sample was mixed with methylene blue solution (10mg / L) in groups, and stirred at a constant speed of 300r / min under 800W ultraviolet light and natural light respectively. After 30min, 1h, and 2h, samples were taken to detect the dye concentration. The test results are as follows:
[0051]
[0052] 0.1g of the obtained powder sample was mixed with rhodamine B solution (10mg / L) in groups, and stirred at a constant speed of 300r / min under 800W ultraviolet light and natural light respectively. After 30min, 1h, and 2h, samples were taken to detect the dye concentration. The test results are as follows:
[0053]
[0054] After testing, the fluorine / carbon co-doped titanium dioxide noble metal cluster photocatalyst powder obtained in Example 1 has ultraviolet light absorption activity and visible light absorption activity. It has certain photocatalytic activity under visible light and can be used as a photocatalyst material to degrade organic dyes under visible light.
[0055] Embodiment 3:
[0056] 1) quantitatively measure 20 mL of ethanol and transfer it to a 100 mL beaker 1, weigh 8 g of titanium tetrachloride and transfer it to the beaker 1, measure 5 mL of hydrochloric acid and add it to the beaker 1, put a magnetic rotor into the beaker 1, and place it on a magnetic stirrer for stirring for later use;
[0057] 2) Take another 100 mL beaker 2, quantitatively weigh 0.25 g of lithium fluoride and add it to beaker 2 with 10 mL of deionized water, transfer it to beaker 1 after mixing, and stir it for 5 min under uniform stirring to obtain a mixed solution;
[0058] 3) The mixed solution obtained above was transferred to a polytetrafluoroethylene liner, placed in a hydrothermal reactor, and reacted at 190° C. in a constant temperature oven for 4 hours to obtain a white or light pink precipitate; the precipitate was transferred to a centrifuge tube, centrifuged 3 times with deionized water, and then centrifuged 2 times with anhydrous ethanol for later use;
[0059] 4) Weigh 0.25g of platinum nitrate and add it to beaker 3, add 10mL of deionized water and stir to dissolve, add 0.15g of n-pentyl mercaptan and the precipitate obtained by centrifugation in step 3), and ultrasonically disperse for 10 minutes. Transfer the dispersed solution to a polytetrafluoroethylene liner, place it in a hydrothermal reactor, and react at a constant temperature of 110°C in a constant temperature oven for 8 hours to obtain a white or off-white precipitate;
[0060] 5) The precipitate was transferred to a centrifuge tube, centrifuged three times with deionized water, and then centrifuged twice with anhydrous ethanol, and dried in a forced air oven at 60°C to obtain an off-white powder sample, which was calcined at 300°C in a nitrogen atmosphere for 1 hour, and then calcined for 1 hour with air introduced to obtain a photocatalyst product.
[0061] 6) Organic dye removal test: 0.1g of the obtained powder sample was mixed with methylene blue solution (10mg / L) in groups, and stirred at a constant speed of 300r / min under 800W ultraviolet light and natural light respectively. After 30min, 1h, and 2h, samples were taken to detect the dye concentration. The test results are as follows:
[0062]
[0063] 0.1g of the obtained powder sample was mixed with rhodamine B solution (10mg / L) in groups, and stirred at a constant speed of 300r / min under 800W ultraviolet light and natural light respectively. After 30min, 1h, and 2h, samples were taken to detect the dye concentration. The test results are as follows:
[0064]
[0065] After testing, the fluorine / carbon co-doped titanium dioxide noble metal cluster photocatalyst powder obtained in Example 1 has ultraviolet light absorption activity and visible light absorption activity. It has certain photocatalytic activity under visible light and can be used as a photocatalyst material to degrade organic dyes under visible light.
[0066] Embodiment 4:
[0067] 1) quantitatively measure 20 mL of ethanol and transfer it to a 100 mL beaker 1, measure 8 g of titanium tetrachloride and transfer it to the beaker 1, measure 5 mL of nitric acid and add it to the beaker 1, put a magnetic rotor into the beaker 1, and place it on a magnetic stirrer for stirring for later use;
[0068] 2) Take another 100mL beaker 2, weigh 0.15g lithium fluoride and add it to beaker 2, add 10mL deionized water and stir to dissolve for 5min, transfer to beaker 1, stir for 5min under uniform stirring to obtain a mixed solution;
[0069] 3) The mixed solution obtained above was transferred to a polytetrafluoroethylene liner, placed in a hydrothermal reactor, and reacted at 150° C. in a constant temperature oven for 4 hours to obtain a white or light pink precipitate; the precipitate was transferred to a centrifuge tube, centrifuged 3 times with deionized water, and then centrifuged 2 times with anhydrous ethanol for later use;
[0070] 4) Weigh 0.15g of silver nitrate and add it to beaker 3, add 10mL of deionized water and stir to dissolve, add 0.2g of mercapto-triethylene glycol-carboxylic acid and the precipitate obtained by centrifugation in step 3), and ultrasonically disperse for 10 minutes. Transfer the dispersed solution to a polytetrafluoroethylene liner, place it in a hydrothermal reactor, and react at a constant temperature of 130°C in a constant temperature oven for 6 hours to obtain a white or off-white precipitate;
[0071] 5) The precipitate was transferred to a centrifuge tube, centrifuged three times with deionized water, and then centrifuged twice with anhydrous ethanol, and dried in a forced air oven at 60°C to obtain an off-white powder sample, which was calcined at 600°C in a nitrogen atmosphere for 1 hour, and then calcined in air for 1 hour to obtain a photocatalyst product.
[0072] 6) Organic dye removal test: 0.1g of the obtained powder sample was mixed with methylene blue solution (10mg / L) in groups, and stirred at a constant speed of 300r / min under 800W ultraviolet light and natural light respectively. After 30min, 1h, and 2h, samples were taken to detect the dye concentration. The test results are as follows:
[0073]
[0074] 0.1g of the obtained powder sample was mixed with rhodamine B solution (10mg / L) in groups, and stirred at a constant speed of 300r / min under 800W ultraviolet light and natural light respectively. After 30min, 1h, and 2h, samples were taken to detect the dye concentration. The test results are as follows:
[0075]
[0076]
[0077] The test shows that the fluorine / carbon co-doped titanium dioxide noble metal cluster photocatalyst powder obtained in this embodiment has ultraviolet light absorption activity and visible light absorption activity. It has certain photocatalytic activity under visible light and can be used as a photocatalyst material to degrade organic dyes under visible light.
Claims
1. A fluorine / carbon co-doped titanium dioxide noble metal cluster photocatalyst material, characterized in that: The fluorine / carbon co-doped titanium dioxide noble metal cluster photocatalyst material is a white or off-white powder, in which the fluorine element is doped into the titanium dioxide crystal lattice in the form of atoms or ions, and the noble metal salt is deposited on the surface of the composite material in the form of nanoclusters, and the surface of the fluorine / carbon co-doped titanium dioxide noble metal cluster photocatalyst material presents a sponge-like wrinkled structure; The preparation method of fluorine / carbon co-doped titanium dioxide noble metal cluster photocatalyst material comprises the following steps: Step (1): add 20 mL to 30 mL of solvent into beaker 1, add 6 g to 8 g of titanium salt thereto, put a magnetic rotor into beaker 1, place beaker 1 on a magnetic stirrer and stir and disperse at a uniform speed for later use; Step (2): Take another beaker 2, add 0.05g-0.25g of fluorine source and 10mL-20mL of solvent and shake well, transfer the solution in beaker 2 to beaker 1, and disperse it under magnetic stirring at room temperature for 5min-10min to obtain a mixed solution; Step (3): transferring the mixed solution obtained in step (2) to a hydrothermal reactor with a polytetrafluoroethylene liner to perform a hydrothermal reaction at a temperature of 130°C-190°C and a hydrothermal reaction time of 2h-6h. After the reaction is completed, a liquid with a light pink precipitate is obtained. The supernatant is removed by standing. The light pink precipitate is washed with water and alcohol for multiple times and then centrifuged and dried in an oven at 40°C-60°C. Step (4): the light pink powder obtained in step (3) is transferred to a beaker 3, 0.05 g to 0.25 g of a noble metal salt, 30 mL of a solvent, and 0.035 g to 0.4 g of a surfactant are added, and after being fully mixed, the mixture is transferred to a hydrothermal reactor lined with polytetrafluoroethylene for a hydrothermal reaction. The hydrothermal reaction temperature is 110° C. to 170° C., and the hydrothermal reaction time is 2 h to 8 h. After the reaction is completed, a liquid with an off-white precipitate is obtained; the surfactant is a thiol ligand; Step (5): centrifuge the liquid with off-white precipitate obtained in step (4) to obtain an off-white powder, wash the off-white powder with water and alcohol for multiple times, and then place it in an oven and dry it at 40°C-60°C for 12-24 hours; Step (6): calcine the preliminary product obtained in step (5) at 300-600° C. in a nitrogen atmosphere for 1-3 h, and continue to calcine for 1-3 h while introducing air to obtain a product, namely, a fluorine / carbon co-doped titanium dioxide noble metal cluster photocatalyst material.
2. The fluorine / carbon co-doped titanium dioxide noble metal cluster photocatalyst material according to claim 1, characterized in that: The titanium salt is one of titanium tetrachloride and tetrabutyl titanate; the fluorine source is one of sodium fluoride, lithium fluoride and hydrofluoric acid; the noble metal salt is one of silver salt and platinum salt; the solvent in steps (1) and (2) is a mixed solution of nitric acid, deionized water and ethanol or a mixed solution of hydrochloric acid, deionized water and ethanol.
3. The fluorine / carbon co-doped titanium dioxide noble metal cluster photocatalyst material according to claim 2, characterized in that: The volume ratio of nitric acid, deionized water and ethanol is: (0.02-0.2):(0.1-0.4):(0.4-0.8), and the volume ratio of hydrochloric acid, deionized water and ethanol is: (0.02-0.2):(0.1-0.4):(0.4-0.8).
4. The fluorine / carbon co-doped titanium dioxide noble metal cluster photocatalyst material according to claim 1, characterized in that: The surfactant is one of n-octyl mercaptan, 2-naphthyl mercaptan, n-pentyl mercaptan, and mercapto-triethylene glycol-carboxylic acid.
Citation Information
Patent Citations
Fluorine-doped titanium dioxide supported noble metal catalyst, preparation method and applications thereof
CN106076375A
Preparation method of low-temperature non-aqueous sol-gel of high-activity carbon-chlorine codoped titanium dioxide visible light catalyst
CN101844084A
Preparation of fluorine and carbon co-doped nano-titanium dioxide visible light photocatalyst
CN101862664A
Cluster-type PtNi alloy nano catalyst and preparation method and application thereof
CN106994352A
Method for loading metal clusters on photocatalyst
CN114042451A